2019
DOI: 10.18203/2349-3259.ijct20193212
|View full text |Cite
|
Sign up to set email alerts
|

Even preoperative carbohydrate loading is too hard? Why RCT’s should not be considered the gold standard for nutrition research in acute hip fracture: results of a feasibility study

Abstract: <p class="abstract"><strong>Background:</strong> Malnutrition is a high-risk co-morbidity in acute hip fracture patients. Pre-operative carbohydrate loading may improve nutritional status and therefore patient outcomes. The feasibility of nutrition focused randomised control trial designs in hip fracture is at best questionable. This study was designed to undertake efficacy testing of pre-operative carbohydrate loading and explore the broader feasibility of conducting randomised controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A low attrition rate of less than 30%, with good patient compliance and high tolerability clearly supported the feasibility of this intervention. In contrast, many studies although acknowledged preoperative carbohydrate loading as relatively simple, inexpensive and low risk, has found feasibility to conduct trials in clinical practice unattainable when it comes to nutrition in hip fracture [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low attrition rate of less than 30%, with good patient compliance and high tolerability clearly supported the feasibility of this intervention. In contrast, many studies although acknowledged preoperative carbohydrate loading as relatively simple, inexpensive and low risk, has found feasibility to conduct trials in clinical practice unattainable when it comes to nutrition in hip fracture [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in gynae-oncology patients reported good compliance and ease of implementation, citing positive concerted effort from staff and patients [ 24 ]. On another note, a few studies found technical and personnel contributory factors which made its implementation challenging [ 22 , 25 ]. Therefore, learning from their experience, we had conducted a protocol briefing with the nursing team very early at the preparation stage with emphasis on the safe consumption up to 2 h prior to operation.…”
Section: Discussionmentioning
confidence: 99%